The effect of empowering leadership and psychological availabiity on individual improvisation: Reflection in China - Luo, Yuxin (2020)
This research is aimed to examine the relationships between empowering leadership and psychological availability on individual improvisation in China. A total of 530 questionnaires were distributed to the employees working at Tencent Co. and only 325 employees are responded, which yield a response rate of 61.3%. All data has been analyzed by using statistical package for social science (SPSS) version 23. The findings showed that both empowering leadership and psychological availability are positively related to individual improvisation. This indicated that when top management empower the employees by giving more flexibility and freedom it can enhance the improvisation of employees. Further, psychological availability can indeed affect improvisation behaviors by improve the psychological perception of employees. Hence, leader manager at organizations or small and medium-sized enterprises can appropriately delegate power to employees appropriately and care about employee’s psychological availability, without affecting work efficiency and management.